Educational Robot Kits: choices for Education in Science - Fornaza, Roseli; Webber, Carine G.; Villas-Boas, Valquíria (Scientia cum Industria, 2016)
Connected to technological innovations, Educational Robot kits gain prominence for their ability to promote interdisciplinary and team work, motivating students participation during learning activities. However, the insertion of the Robotics in education also brings challenges of diverse natures. The first challenge consists on the choice of the most appropriate robot kit regarding its resources, restrictions and the necessity of pedagogical support to educators. In order to take decisions, technical and educational information are necessary. To contribute to this matter, this work presents and compares three Educational Robot kits to schoolar use. http://dx.doi.org/10.18226/23185279.v3iss3p142